A UNIFIED DIGITAL ECOSYSTEM APPROACH TO ENTERPRISE MANAGEMENT AND DIGITAL SECURITY IN THE DIGITAL ECONOMY - Khalilov Bekzod Akhmatovich (Scholar Express Journals, 2025)
This article provides a scientific analysis of issues related to enterprise management and digital security in the context of the digital economy, based on information and communication technologies (ICT). Within the framework of the study, an approach aimed at organizing management processes, internal and external security, and operational monitoring through a unified digital ecosystem of enterprises is substantiated. This approach enables the integration of managerial decision-making, risk identification and control, and business process automation within a single digital environment. The article scientifically demonstrates that the coordinated application of digital technologies such as CRM, ERP, PLM, CALS, and SMART-ERP constitutes a key factor in improving enterprise management efficiency and strengthening economic security. The research findings provide a methodological basis for developing practical recommendations to enhance management activities and security processes in enterprises through a digital ecosystem–based approach.
Keywords: unified digital ecosystem; digital economy; enterprise management